2015
DOI: 10.4236/ajps.2015.69139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron Soil Application on Nutrients Efficiency in Tobacco Leaf

Abstract: The present study was based on the general hypothesis that boron may affect the accumulation and utilization of other nutrients in plant. For this purpose a field experiment was carried out to find out the influence of boron on the different nutrients content in FCV tobacco (Nicotiana tabacum L.) at TRS Khan Garhi, Mardan, during 2010-2011. Two varieties TM-2008 and Speight G-28 were tested and six levels of boron (0, 0.5, 1, 2, 3 and 5 kg•ha −1 ) were applied in the form of boric acid, in randomized complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
1
6
0
1
Order By: Relevance
“…It is mainly due to the complex dynamics of this nutrient with low mobility within the phloem (Calonego et al, 2010;Mantovani et al, 2013), but with high mobility in soil, especially when applied in the form of boric acid, with high solubility in water and low reactivity with the soil, making it susceptible to leaching (Trautmann et al, 2014). Ali et al (2015), applied six levels of boron (0, 0.5, 1, 2, 3 and 5 kg ha -1…”
Section: Discussionmentioning
confidence: 99%
“…It is mainly due to the complex dynamics of this nutrient with low mobility within the phloem (Calonego et al, 2010;Mantovani et al, 2013), but with high mobility in soil, especially when applied in the form of boric acid, with high solubility in water and low reactivity with the soil, making it susceptible to leaching (Trautmann et al, 2014). Ali et al (2015), applied six levels of boron (0, 0.5, 1, 2, 3 and 5 kg ha -1…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus and B accumulation in grains and straw of wheat plants enhanced considerably at each P level in relation to increasing B levels. Ali et al (2015) have reported the positive effect of B addition on the P concentration in tobacco leaves. In barley, increased B, N, P, K and Na contents and decreased Ca and Mg contents under B application have been observed by Singh and Singh (1983).…”
Section: Discussionmentioning
confidence: 98%
“…pada tanaman telah diperlihatkan memberi respon yang positif pada pertumbuhan dan produksi tanaman (Herlina dan Pramesti, 2004). Selain itu, mekanisme sintesa protein, yang merupakan komponen senyawa kimia penting yang dibutuhkan tanaman dalam proses metabolismenya, dapat berlangsung dengan baik dengan pemberian Boron pada tanaman (Ali et al, 2015). Pemupukan Boron dengan konsentrasi tertentu juga diyakini berperan dalam membantu penyerapan dan transport fotosintat yang lebih baik (Mitra, 2015).…”
Section: Pendahuluanunclassified